Review of the temperature and holding time effects on hydroxyapatite fabrication from the natural sources - Akhlis Rahman Nurhidayat; A. P Bayuseno; Rifky Ismail; Rilo Berdin Taqriban (Center for Biomechanics, Biomaterials, Biomechantronics and Biosignal Processing (CBOIM3S), 2021)
Biomaterial development is currently being carried out to help people who have daily needs. Hydroxyapatite has biocompatibility properties and suitables for the use as a biomaterial. Hydroxyapatite can be found in natural sources sometimes as waste. One of the hydroxyapatite fabrication methods is calcination process. Calcination and sintering are used to obtain the desired Ca/P ratio of the hydroxyapatite. This paper reviews several research which have been published by researchers to withdraw the connection during calcination process, with respect to the temperature and holding time effects on hydroxyapatite fabrication from the natural organism. The effect of temperature and holding time determines the yield of Ca/P ratio which affects the resulting mechanical properties. Choosing the right temperature and holding time will produce Ca/P which meets the standard